The Implementation of ‘Comic Life’ Through Directed Reading Activities to Increase Students’ Reading Comprehension - Suardi Suardi (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
The research was conducted to know the effectiveness of the use of Comic Life through Directed Reading Activities to increase students’ reading comprehension. It covered students’ literal comprehension, interpretive comprehension and applied comprehension. And to find out the students’ interest in teaching reading comprehension toward the application of Comic Life through Directed Reading Activities to increase students’ reading comprehension. The research method employed was quasi experimental. This research was designed into two groups, namely experimental group and control group. Each group consisted of 32 students. The sample was chosen by applying cluster sampling technique. The researcher used multiple choice of reading test both in experimental and control groups. The data obtained through the test were analyzed by using inferential statistic through SPSS 16.0 program. The research findings showed that Comic Life through Directed Reading Activities gave higher contribution to the students’ reading comprehension. The mean score of pre- test of the experimental and control group was not significantly different. The mean score of post- test of the experimental group was higher than the control group (75.62 > 56.87). Besides, all the three level of comprehension improved after the treatment, the literal level got the highest improvement with 9.69 point. It was followed by interpretive level which got 21.25 point and applied level which got 42.19 point improvement. This led to the conclusion that the application of Comic Life through Directed Reading Activities increased the students’ reading comprehension. It means that the use of Comic Life through Directed Reading Activities in teaching reading is very effective to increase the students’ reading comprehension.